River Hydrology Analysis For Micro Hydro Power Plant - Yulia; Akmal; Yeni, Manovri; Fata Akram, Annas (SEULANGA SYSTEM PUBLISHER, 2024)
The Micro Hydro Power Plant (PLTMH) is a generator capable of fulfilling the electrical requirements of isolated regions. PLTMH serves as an alternative means of generating electrical energy for the community. This power facility offers numerous advantages, particularly for remote areas across Indonesia. Water is a crucial energy resource due to its ability to generate electricity, a cost-effective and environmentally friendly kind of energy. The micro-hydro type PLTMH (0.5–100 kilowatts) in Aceh Province is the Lhoong PLTMH, which was built with assistance from PT. Coca-Cola in 2005. This PLTMH is located in Krueng Kala Village, Lhoong District, Aceh Besar Regency. This research aims to determine the availability of the Krueng Kala Lhoong PLTMH's flow rate and the availability of power and energy produced by the Krueng Kala Lhoong PLTMH to meet the electricity needs of Lhoong residents. It is hoped that the benefits of this research will be able to provide development and knowledge, especially in the field of pyrotechnics, and can become reference material for further study, providing information about micro hydropower plants, especially the Krueng Kala Lhoong PLTMH. The research utilizes the Pearson III Log Method to calculate maximum rainfall frequency and Fj Mock for reliable discharge calculation. The research results showed that the full rain discharge with a return period of 25 years was 1152.68 mm/hour. The total potential evapotranspiration (ET0) value occurred in March, reaching 6,649 mm/day. The mainstay discharge with a probability of 85% is Q85% = 0.24 m3/second, obtaining power of 27,914 kW and energy for a year of 20787,644 kWh. The calculation results conclude that the Krueng Kala power plant is still classified as a PLTMH, producing power below 100 kW and generating an annual energy of 20,787,644 kWh. The electricity can be distributed to Meunasah Krueng Kala Village, Baroeh Krueng Kala Village, Tunong Krueng Kala Village, and small enterprises in these three communities.